(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2024)
Introduction: A very simple, cheap, easily available and non-invasive approach has made routine semen analysis the most important tool for diagnosis of male fertility. Objective: To determine I) the percentage of abnormality in semen parameters present in the husbands of infertile couples, II) the effect of occupation on abnormal parameters and iii) the effect of increasing age on semen quality. Methods: A cross sectional retrospective study was designed in a period of April 2019 to March 2020 on the basic semen analysis reports of the husbands of infertile couples reporting to the fertility clinic of a tertiary level military hospital of Bangladesh. Results: Out of 851 couples only 372 were excluded from female cause. At least 44% husbands showed at least one abnormality in their semen parameters according to WHO 2010 criteria and out of them 3.8% were azospermic. Almost all abnormalities showed more severity in the patients reporting from non-military background. Significant differences were demonstrated in the mean values in semen parameters like volume, concentration and motility between different occupational groups. Mean values of sperm concentration between different age groups showed significant changes. Values of other parameters also showed gradual decrease with increase of age but differences were not significant. Conclusions: The present study showed that even 56% normozoospermic husbands can be partners of infertile couples. Occupation and age affect male fertility. JAFMC Bangladesh. Vol 19, No 1 (June) 2023: 66-71